Sociodemographic determinants of disease severity in a public healthcare system - Leon Pomberger; Sophia Anna Reifeltshammer; Sabrina Stojanov; Andreas Honeder; Matthias Bolz; Nino Hirnschall (Wiener klinische Wochenschrift, 2026)
Summary Purpose To assess whether sociodemographic factors are associated with disease severity in patients with keratoconus treated at a tertiary care center within a publicly funded healthcare system. Setting Kepler University Clinic and Johannes Kepler University, Linz, Austria. Methods This monocentric cross-sectional study assessed socioeconomic factors, quality of life, and objective measurement parameters in patients with keratoconus. Clinical data included best-corrected distance visual acuity (BCDVA) and corneal parameters using anterior segment optical coherence tomography (AS-OCT), including anterior and posterior maximum corneal curvature (K max ), minimum pachymetry (Th min ), and epithelial thickness index (ETI). Sociodemographic factors and access-to-care variables were assessed using a structured questionnaire. Disease severity and patient-reported outcomes were analyzed according to the Austrian urban-rural typology in order to explore regional and sociodemographic differences. Quality of life and subjective symptoms were assessed using the Rasch-validated Keratoconus Outcomes Research Questionnaire (KORQ). Results A total of 105 patients (70.48% male; 29.52% female) were included in this study. The highest anterior K max values were observed in patients from medium-sized urban centers (right eye 55.79 ± 13.43 D; left eye 59.78 ± 13.30 D). Visual acuity was lowest for major and medium sized urban centers (right eye 0.41 ± 0.45 logMAR; left eye 0.47 ± 0.38 logMAR). KORQ Scores were highest in medium sized (51.71 ± 7.21 points) and major urban centers (47.38 ± 14.08 points), indicating greater patient-reported disease burden. Conclusion Sociodemographic factors may contribute to differences in disease severity among keratoconus patients, even within a publicly funded healthcare system. Universal health coverage alone may not ensure equitable access to timely diagnosis and specialized care. Larger studies with multivariable adjustment are needed for underlying these observations.